Positively charged nanofiltration membrane for efficiently separating metal ions

Through the combination of graphene, SiO2 and PEI, an efficient positive charge nanofiltration membrane was prepared, which solved the problems of low separation efficiency and poor durability of existing nanofiltration membranes, and achieved efficient metal ion separation and long-term stable performance.

CN119565399AActive Publication Date: 2025-03-07NANJING TECH UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411797233.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing positive charge nanofiltration membranes have shortcomings in metal ion separation efficiency and durability, with low separation efficiency and poor membrane durability.

Method used

By combining materials such as graphene, SiO2 and PEI, a positively charged nanofiltration membrane modified with PEI modified polyglycidylamine modified based on graphene/SiO2 ultrafiltration membrane base membrane was prepared, which imparts positive charge to the membrane surface and improves separation efficiency and durability.

Benefits of technology

The nanofiltration membrane can have a retention rate of more than 97% of divalent metal ions, and the flux attenuation rate is as low as 3%-8%/12 h, which significantly improves separation efficiency and durability. It is suitable for seawater desalination, wastewater treatment and resource recovery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a positively charged nanofiltration membrane for efficiently separating metal ions. According to the method, graphene and SiO are used for modifying a polysulfone ultrafiltration membrane base membrane, then polyethyleneimine (PEI) modified by polyglycidyl amine (PGAM) is grafted on the modified ultrafiltration membrane, and the positively charged nanofiltration membrane is successfully prepared. The nanofiltration membrane integrates the advantages of high strength and hydrophilicity of graphene and SiO, and positive charges are given to the surface of the membrane through the modification effect of polyethyleneimine and polyglycidyl amine. The prepared positively-charged nanofiltration membrane significantly improves the separation efficiency and durability of metal ions, and has significant application value and broad prospects in the key fields of seawater desalination, wastewater treatment, resource recovery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane separation, in particular to a method for preparing a positively charged modified nanofiltration membrane for efficient metal ion separation. Background Art

[0002] With the rapid development of industrialization and urbanization, the pollution problem of metal ions in water bodies has become increasingly serious. Heavy metal ions are highly toxic and difficult to degrade. They cause great harm to the ecological environment and human health through migration and transformation in the biosphere. Traditional methods for removing heavy metal ions mainly include chemical precipitation, ion exchange, adsorption, etc., but these methods have disadvantages such as low treatment efficiency, high cost, and great impact on the environment. Compared with traditional methods for removing heavy metal ions, positively charged nanofiltration membranes usually have the same positive charge as heavy metal ions, which makes the charge repulsion more obvious, has a higher interception rate for multivalent cations and positively charged pollutants, and has high water permeability. By intercepting divalent or multivalent cations, it can efficiently remove heavy metals in wastewater while retaining trace elements that are beneficial to the human body.

[0003] At present, research has been conducted at home and abroad on how to better separate metal ions using positively charged nanofiltration membranes. For example, patent CN202410013910 uses quaternary ammonium salt monomers prepared from vinylamine salts and 2-bromoethylamine hydrobromide to obtain a positively charged nanofiltration membrane through interfacial polymerization, which has a retention rate of 95.49% for CaCl2 and a flux of 128.34 L·m -2 ·h -1 MPa -1 , the interception rate of MgCl2 can reach 96.26%, and the flux is 137.71 L·m -2 ·h -1 MPa -1 etc. Patent CN115364684A provides a method for preparing a high-throughput positively charged nanofiltration membrane. Through specific chemical treatment and heat treatment steps, the positively charged nanofiltration membrane is prepared, and its water permeation flux is 70 L / m²·h·bar. The retention rate of various dyes and drugs is above 90%. After 12 hours of continuous separation test, the membrane retention rate remains basically unchanged, but the water permeation flux decreases by about 10%. The above technologies have obvious advantages, but there are still problems such as low separation efficiency and weak membrane durability.

[0004] This patent provides a method for preparing a positively charged nanofiltration membrane with efficient metal ion separation function. By combining materials such as graphene, SiO2 and PEI, the membrane surface is successfully given a positive charge, which significantly improves the separation efficiency and durability. The nanofiltration membrane prepared by this method has high strength and hydrophilicity, and has a retention rate of more than 97% for divalent metal ions, and the flux attenuation rate is as low as 3%-8% / 12 h (the ratio of flux attenuation every 12 hours). This nanofiltration membrane has broad application prospects in the fields of seawater desalination, wastewater treatment and resource recovery, and is of great significance to solving the problem of metal ion pollution. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a PEI-modified polyglycidylamine-modified positively charged nanofiltration membrane based on a graphene / SiO2-modified polysulfone ultrafiltration membrane base membrane, aiming to improve the separation efficiency and durability of the nanofiltration membrane, and is particularly suitable for the efficient separation of metal ions.

[0006] (1) Graphene powder and mesoporous SiO2 powder are mixed in a mass ratio of 1:1-2:1, placed in an organic solvent (such as N,N-dimethylacetamide), and dispersed by ultrasonication for 1-3 hours to form a uniform dispersion.

[0007] (2) Add polysulfone, polyvinylidene fluoride and polyvinyl pyrrolidone into a reaction kettle at a mass ratio of 5:1:1-7:1:1, stir evenly and heat to a temperature in the range of 100-150°C, and keep the temperature for 1-4 hours.

[0008] (3) Add NN-methylacetamide and inorganic salts (sodium sulfate, sodium chloride) to the reactor in sequence and continue stirring for 10-30 minutes; (4) adding N-methylpyrrolidone and polyethylene glycol to the reaction kettle in sequence and continuing stirring for 30-50 minutes; (5) pouring the dispersion obtained in step (1) into a reaction kettle, keeping warm and continuing stirring for 1 hour to prepare a primary casting solution; (6) vacuum degassing the primary casting solution at a pressure range of 1-5 MPa and a temperature of 80-180° C. to prepare a graphene / silicon dioxide polysulfone casting solution; (7) The above-mentioned casting solution is prepared into a modified polysulfone ultrafiltration membrane base membrane by a phase inversion method. The casting solution after standing is poured onto a glass plate, and a membrane with uniform thickness is obtained at a uniform speed using a scraper, and then placed in a pure water coagulation bath for phase inversion to obtain a modified base membrane, which is stored in deionized water for later use.

[0009] Step 2: Pretreatment of modified base film (1) Surface cleaning: Use a mild organic solvent (such as ethanol, isopropanol) to soak and rinse the polysulfone ultrafiltration membrane, and then rinse it repeatedly with deionized water for 3-5 times to remove impurities, oil stains and residual chemicals that may exist on the surface to ensure that the membrane surface is clean.

[0010] (2) Surface activation: The membrane surface was treated with a potassium permanganate-sulfuric acid mixed solution and soaked for 1 hour. The reactive groups on the surface of the polysulfone ultrafiltration membrane were increased by chemical oxidation, and active groups such as carboxyl and hydroxyl groups were introduced into the membrane surface.

[0011] Step 3: Preparation of PGAM and PEI reaction compounds (1) Selection of reaction conditions: PGAM and PEI are mixed in a dimethyl sulfoxide (DMSO) solvent at a molar ratio of 0.5:3-2:3, the reaction temperature is set at 40-80 °C, the stirring speed is 300-600 rpm, and an appropriate amount of sodium hydroxide (accounting for 1% of the total mass of PGAM and PEI) is added as an alkaline catalyst to accelerate the ring-opening reaction of the epoxy group. The reaction time is 1-3 hours.

[0012] (2) Product purification: After the reaction is completed, the solvent is removed by reduced pressure distillation at 60 °C and 0.08 MPa using a rotary evaporator. The crude product is then dissolved in deionized water and purified by dialysis (dialysis bag molecular weight cutoff 500-1000 Da). The deionized water is replaced every 4-6 hours and the dialysis is performed for 24-48 hours to obtain a pure PEI-PGAM reaction compound.

[0013] Step 4: Grafting reaction process (1) Preparation of grafting solution: The purified PEI-PGAM reaction compound is dissolved in a phosphate buffer solution (pH 7.5) to prepare a grafting solution with a concentration of 5%-20%.

[0014] (2) Grafting reaction operation: The pretreated polysulfone ultrafiltration membrane is immersed in the grafting solution and reacted at 60-90 °C for 2-10 h. During the grafting process, the amino groups in the PEI-PGAM reaction compound react with the carboxyl and hydroxyl groups on the surface of the polysulfone ultrafiltration membrane to achieve grafting.

[0015] Step 5: Post-processing After the grafting reaction is completed, the nanofiltration membrane is removed and rinsed with a large amount of deionized water for 10-15 minutes, 3-5 times, to remove the unreacted PGAM-PEI compound and other impurities. The membrane is then dried at 40-60 ° C for 3 hours to allow the grafted compound to stably exist on the membrane surface, and the final positively charged nanofiltration membrane is obtained.

[0016] Through the composite of graphene and SiO2, the present invention realizes the interaction of the two-dimensional structure of graphene and the porous structure of SiO2 to form a special network structure, providing more channels for water molecules to pass through, reducing the permeation resistance of the membrane, and enhancing the interception capacity, mechanical strength and hydrophilicity of the membrane for different molecules. At the same time, the introduction of PEI-PGAM successfully makes the membrane surface positively charged, enhancing the adsorption and separation capacity of metal ions. According to the test, the interception rate of the modified nanofiltration membrane for divalent metal ions (such as copper ions, lead ions, chromium ions, etc.) can reach more than 97%, the tensile strength reaches 5.8 MPa, which is 45% higher than that of the traditional positively charged nanofiltration membrane, and the contact angle reaches 40°, which is 10° lower than that of the traditional positively charged nanofiltration membrane. In the long-term filtration experiment, the membrane flux attenuation rate is as low as 3%-8% / 12 h, which is about 20% lower than that of the traditional membrane. The nanofiltration membrane performs well in separating metal ions and has good separation performance and durability.

[0017] (1) Efficient separation performance: The positively charged nanofiltration membrane prepared by PEI and PGAM modification has a retention rate of more than 97% for divalent metal ions (such as copper ions, lead ions, etc.), which significantly improves the separation efficiency of metal ions. The modification of graphene and SiO2 increases the hydrophilicity of the material, thereby improving the flux of the membrane; (2) Excellent mechanical strength and durability: The composite of graphene and SiO2 improves the mechanical strength of the membrane (≥5.8 MPa). During long-term use, the membrane flux attenuation rate is as low as 3%-8% / 12 h, extending the service life of the membrane. DETAILED DESCRIPTION Example

[0018] (1) Graphene powder and mesoporous SiO2 powder were mixed in a mass ratio of 1:1 and ultrasonically dispersed for 2 hours to form a dispersion. Polysulfone, polyvinylidene fluoride, and polyvinyl pyrrolidone were added to a reactor in a mass ratio of 5:1:1, heated to 120 °C and kept warm for 2 hours. NN-methylacetamide and sodium chloride were added, stirred for 20 minutes, and then N-methylpyrrolidone and polyethylene glycol were added and stirred for 40 minutes. The above dispersion was poured into a reactor and kept warm and stirred for 1 hour. Vacuum degassing was performed at a pressure of 3 MPa and a temperature of 120 °C to obtain a casting solution. A film was scraped on a glass plate using a scraper, and then immersed in a coagulation bath to obtain a modified base membrane by a phase inversion method.

[0019] (2) Soak the polysulfone ultrafiltration membrane in ethanol and rinse it with deionized water for 3-5 times. Soak the membrane rinsed with deionized water in a potassium permanganate-sulfuric acid mixed solution (potassium permanganate concentration is 0.1 mol / L, sulfuric acid concentration is 1 mol / L) for 1 hour.

[0020] (3) PGAM and PEI were mixed in DMSO at a molar ratio of 1:3, and 1% sodium hydroxide was added, and the mixture was reacted at 60°C for 2 hours. The reaction solution was distilled under reduced pressure at 60°C and 0.08 MPa, and purified by dialysis for 24 hours to obtain the grafted product.

[0021] (4) The purified PEI-PGAM reaction compound was dissolved in a phosphate buffer solution (pH 7.5) to prepare a grafting solution with a concentration of 10%. The pretreated polysulfone ultrafiltration membrane was immersed in the grafting solution and reacted at 75°C for 6 hours.

[0022] (5) After the grafting reaction is completed, the nanofiltration membrane is removed and rinsed with a large amount of deionized water for 10 minutes and three times to remove the unreacted PGAM-PEI compound and other impurities. The membrane is then dried at 50 °C for 3 hours to allow the grafted compound to stably exist on the membrane surface, thereby obtaining the final positively charged nanofiltration membrane.

[0023] (6) The performance of the positively charged nanofiltration membrane prepared in Example 1 was tested. The tensile strength of the membrane can reach 5.4 MPa, and the contact angle can reach 43°. The nanofiltration membrane has a CuCl2 rejection rate of 98.49% and a flux of 123.21 L·m -2 ·h -1 MPa -1 , the rejection rate of PbCl2 was 97.25% and the flux was 137.70 L·m -2 ·h -1 MPa -1 The retention rate of CaCl2 was 97.42% and the flux was 132.56 L·m -2 ·h -1 MPa -1 The interception rate of MgCl2 can reach 97.32%, and the flux is 139.53 L·m -2 ·h -1 MPa -1 , the rejection rate of NaCl was 71.24% and the flux was 95.88 L·m -2 ·h -1 MPa -1 , the membrane flux decay rate is 7% / 12 h. Example

[0024] (1) Graphene powder and mesoporous SiO2 powder were mixed in a mass ratio of 1.2:1 and ultrasonically dispersed for 2.5 hours to form a dispersion. Polysulfone, polyvinylidene fluoride, and polyvinyl pyrrolidone were added to a reactor in a mass ratio of 5:1:1, heated to 120 °C and kept warm for 2 hours. NN-methylacetamide and sodium chloride were added, stirred for 20 minutes, and then N-methylpyrrolidone and polyethylene glycol were added and stirred for 40 minutes. The above dispersion was poured into a reactor and kept warm and stirred for 1 hour. Vacuum degassing was performed at 3 MPa pressure and 120 °C to obtain a casting solution. A film was scraped on a glass plate using a scraper, and then immersed in a coagulation bath to obtain a modified base membrane by a phase inversion method.

[0025] (2) Soak the polysulfone ultrafiltration membrane in ethanol and rinse it with deionized water for 3-5 times. Soak the membrane rinsed with deionized water in a potassium permanganate-sulfuric acid mixed solution (potassium permanganate concentration is 0.1 mol / L, sulfuric acid concentration is 1 mol / L) for 1 hour.

[0026] (3) PGAM and PEI were mixed in DMSO at a molar ratio of 1:3, 1% sodium hydroxide was added, and the mixture was reacted at 60°C for 2 hours. The reaction solution was distilled under reduced pressure at 60°C and 0.08 MPa, and purified by dialysis for 24 hours to obtain the grafted product.

[0027] (4) The purified PEI-PGAM reaction compound was dissolved in a phosphate buffer solution (pH 7.5) to prepare a grafting solution with a concentration of 10%. The pretreated polysulfone ultrafiltration membrane was immersed in the grafting solution and reacted at 75°C for 6 hours.

[0028] (5) After the grafting reaction is completed, the nanofiltration membrane is removed and rinsed with a large amount of deionized water for 10 minutes and three times to remove the unreacted PGAM-PEI compound and other impurities. The membrane is then dried at 50 °C for 3 hours to allow the grafted compound to stably exist on the membrane surface, thereby obtaining the final positively charged nanofiltration membrane.

[0029] (6) The performance of the positively charged nanofiltration membrane prepared in Example 2 was tested. The tensile strength of the membrane can reach 5.8 MPa, and the contact angle can reach 44°. The nanofiltration membrane has a CuCl2 rejection rate of 97.784% and a flux of 123.65 L·m -2 ·h -1 MPa -1 , the rejection rate of PbCl2 was 97.53% and the flux was 137.91 L·m -2 ·h -1 MPa -1 The retention rate of CaCl2 was 97.64% and the flux was 94.65 L·m -2 ·h -1 MPa-1 The interception rate of MgCl2 can reach 97.62%, and the flux is 139.33L·m -2 ·h -1 MPa -1 The rejection rate of NaCl was 71.46% and the flux was 95.93 L·m -2 ·h -1 MPa -1 , the membrane flux decay rate is 3% / 12 h. Example

[0030] Step 1: Preparation of graphene / SiO2 modified polysulfone ultrafiltration membrane base membrane (1) Graphene powder and mesoporous SiO2 powder were mixed in a mass ratio of 1:1 and ultrasonically dispersed for 2 hours to form a dispersion. Polysulfone, polyvinylidene fluoride, and polyvinyl pyrrolidone were added to a reactor in a mass ratio of 6:1:1, heated to 120 °C and kept warm for 2 hours. NN-methylacetamide and sodium chloride were added, stirred for 20 minutes, and then N-methylpyrrolidone and polyethylene glycol were added and stirred for 40 minutes. The above dispersion was poured into a reactor and kept warm and stirred for 1 hour. Vacuum degassing was performed at 3 MPa pressure and 120 °C to obtain a casting solution. A film was scraped on a glass plate using a scraper, and then immersed in a coagulation bath to obtain a modified base membrane by a phase inversion method.

[0031] (2) Soak the polysulfone ultrafiltration membrane in ethanol and rinse it with deionized water for 3-5 times. Soak the membrane rinsed with deionized water in a potassium permanganate-sulfuric acid mixed solution (potassium permanganate concentration is 0.1 mol / L, sulfuric acid concentration is 1 mol / L) for 1 hour.

[0032] (3) PGAM and PEI were mixed in DMSO at a molar ratio of 1.2:3, and 1.5% sodium hydroxide was added, and the mixture was reacted at 60°C for 2 hours. The reaction solution was distilled under reduced pressure at 60°C and 0.08 MPa, and purified by dialysis for 24 hours to obtain the grafted product.

[0033] (4) The purified PEI-PGAM reaction compound was dissolved in a phosphate buffer solution (pH 7.5) to prepare a grafting solution with a concentration of 15%. The pretreated polysulfone ultrafiltration membrane was immersed in the grafting solution and reacted at 80°C for 7 hours.

[0034] (5) After the grafting reaction is completed, the nanofiltration membrane is removed and rinsed with a large amount of deionized water for 10 minutes and three times to remove the unreacted PGAM-PEI compound and other impurities. The membrane is then dried at 50 °C for 3 hours to allow the grafted compound to stably exist on the membrane surface, thereby obtaining the final positively charged nanofiltration membrane.

[0035] (6) The performance of the positively charged nanofiltration membrane prepared in Example 3 was tested. The tensile strength of the membrane can reach 5.8 MPa and the contact angle can reach 38°. The retention rate of the nanofiltration membrane for CuCl2 is 98.36% and the flux is 124.19 L·m -2 ·h -1 MPa -1 , the rejection rate of PbCl2 was 97.25% and the flux was 137.78 L·m -2 ·h -1 MPa -1 The retention rate of CaCl2 was 96.98% and the flux was 94.78 L·m -2 ·h -1 MPa -1 The interception rate of MgCl2 can reach 97.24% and the flux is 139.54L·m -2 ·h -1 MPa -1 , the rejection rate of NaCl was 72.15% and the flux was 96.22 L·m -2 ·h -1 MPa -1 , the membrane flux decay rate is 4% / 12 h. Example

[0036] (1) Graphene powder and mesoporous SiO2 powder were mixed in a mass ratio of 1:1 and ultrasonically dispersed for 2 hours to form a dispersion. Polysulfone, polyvinylidene fluoride, and polyvinyl pyrrolidone were added to a reactor in a mass ratio of 5:1:1, heated to 120 °C and kept warm for 2 hours. NN-methylacetamide and sodium chloride were added, stirred for 20 minutes, and then N-methylpyrrolidone and polyethylene glycol were added and stirred for 40 minutes. The above dispersion was poured into a reactor and kept warm and stirred for 1 hour. Vacuum degassing was performed at 3 MPa pressure and 120 °C to obtain a casting solution. The film was scraped on a glass plate with a scraper and then immersed in a coagulation bath to obtain a modified base membrane by a phase inversion method.

[0037] (2) Soak the polysulfone ultrafiltration membrane in ethanol and rinse it with deionized water for 3-5 times. Soak the membrane rinsed with deionized water in a potassium permanganate-sulfuric acid mixed solution (potassium permanganate concentration is 0.1 mol / L, sulfuric acid concentration is 1 mol / L) for 1 hour.

[0038] (3) PGAM and PEI were mixed in DMSO at a molar ratio of 0.8:3, 1% sodium hydroxide was added, and the mixture was reacted at 60°C for 2 hours. The reaction solution was distilled under reduced pressure at 60°C and 0.08 MPa, and purified by dialysis for 24 hours to obtain the grafted product.

[0039] (4) The purified PEI-PGAM reaction compound was dissolved in a phosphate buffer solution (pH 7.5) to prepare a grafting solution with a concentration of 10%. The pretreated polysulfone ultrafiltration membrane was immersed in the grafting solution and reacted at 75°C for 6 hours.

[0040] (5) After the grafting reaction is completed, the nanofiltration membrane is removed and rinsed with a large amount of deionized water for 10 minutes and three times to remove the unreacted PGAM-PEI compound and other impurities. The membrane is then dried at 50 °C for 3 hours to allow the grafted compound to stably exist on the membrane surface, thereby obtaining the final positively charged nanofiltration membrane.

[0041] (6) The performance of the positively charged nanofiltration membrane prepared in Example 4 was tested. The tensile strength of the membrane can reach 5.8 MPa, and the contact angle can reach 42°. The nanofiltration membrane has a CuCl2 rejection rate of 97.12% and a flux of 122.32 L·m -2 ·h -1 MPa -1 , the rejection rate of PbCl2 was 97.55% and the flux was 136.98 L·m -2 ·h -1 MPa -1 The retention rate of CaCl2 was 97.32% and the flux was 93.88 L·m -2 ·h -1 MPa -1 The interception rate of MgCl2 can reach 97.12%, and the flux is 138.83L·m -2 ·h -1 MPa -1 The rejection rate of NaCl was 70.11% and the flux was 95.82 L·m -2 ·h -1 MPa -1 , the membrane flux decay rate is 6% / 12 h.

Claims

1. A method for preparing a positively charged nanofiltration membrane for efficiently separating metal ions, characterized in that: The preparation method comprises: using graphene and SiO2 in the preparation of a polysulfone ultrafiltration membrane base membrane by a phase inversion method, then activating the surface of the base membrane, using the amine group (-NH2) in the PEI molecule as a nucleophilic agent to attack the epoxy group in the PGAM molecule, and a nucleophilic addition reaction occurs to form an intermediate. Subsequently, after an elimination reaction, the epoxy group opens to form a new covalent bond, connecting PEI and PGAM to form a polymer PEI-PGAM required for modifying the surface of the base membrane, and then the active group amine group in the PEI-PGAM reaction compound undergoes a condensation reaction with the active group (carboxyl or hydroxyl) on the surface of the polysulfone ultrafiltration membrane, thereby achieving the grafting of the polymer to the surface of the activated polysulfone ultrafiltration membrane base membrane. Finally, after post-treatment, the grafted compound is stably present on the membrane surface to obtain the final positively charged nanofiltration membrane; wherein, the mass ratio of graphene to SiO2 is 1:1-2:1, and the ultrasonic dispersion time is 1-3 hours; the mass ratio of polysulfone, polyvinylidene fluoride, and polyvinyl pyrrolidone is 5:1:1-7:1:1, and the solvent is N,N-dimethylacetamide; PGAM and PEI are in a molar ratio of 0.5:3-2:3, the reaction temperature is 40-60°C, and the reaction time is 1-3 hours; the grafting reaction temperature is 60-90°C, and the reaction time is 2-10 hours; after the membrane surface is modified, it is dried at 40-60°C.

2. A method for preparing a high-performance positively charged nanofiltration membrane as claimed in claim 1, characterized in that: The mild organic solvent used for surface cleaning pretreatment of the polysulfone ultrafiltration membrane is one of ethanol and isopropanol.

3. A method for preparing a high-performance positively charged nanofiltration membrane as claimed in claim 1, characterized in that: The solvent selected in the casting solution is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.

4. A method for preparing a high-performance positively charged nanofiltration membrane as claimed in claim 1, characterized in that: The inorganic salt added to the casting solution is one of sodium sulfate and sodium chloride.

5. A method for preparing a high-performance positively charged nanofiltration membrane as claimed in claim 1, characterized in that: The nanofiltration membrane is prepared by modifying the polysulfone ultrafiltration membrane base membrane with graphene and SiO2, and then grafting PEI (polyethyleneimine) modified by PGAM (polyglycidylamine) on the modified ultrafiltration membrane.

Citation Information

Patent Citations

  • High-flux positively charged nanofiltration membrane and preparation method thereof

    CN115364684A

  • Preparation method of positively charged nanofiltration membrane for treating industrial wastewater containing high-concentration cations

    CN117839445A

  • Three-dimensional graphene / black titanium dioxide composite material and preparation method and application thereof

    CN110385118A

  • Ceramic go / PEI nanomembrane by layer-by-layer assembly based on covalent bond using EDC chemistry and method for manufacturing the same

    US20220194869A1